Relationship quality between Portuguese wine producers and Chinese distributors insight and recommendations - Loureiro, S. M. C. (2018)
The current chapter aims to: (1) present the core constructs of relationship quality (RQ) that may differentiate positively or negatively the business-to-business relationships; (2) give an overview of major wine producer countries (old world and new world) from the perspective of the Chinese market; (3) highlight the characteristics of the Chinese wine market, as an opportunity for Portuguese wine producers; and (iv) give insight and recommendations to develop a sustainable exchange relationship with a Chinese distributor. The literature review is based on the scientific publications gathered by searching the database of scientific journals. As for the empirical requirements, secondary data is collected from official statistical reports and primary data by carrying out interviews with wine producers. Findings highlight the relevance in establishing quality relationships and understanding the Chinese market and culture. Four factors are considered as the most relevant in the RQ: Trust; Interdependence; Cooperation; and Long-term Relationship. Regarding difficulties in working with the Chinese market, three factors emerge: physical distance, knowledge about Portugal and its grape varieties, and communication and culture. The chapter also provides recommendations to help understand how to create and maintain a producer–distributor relationship in China.